EKSPLORASI IDE-IDE MATEMATIKA PADA KESENIAN REYOG TULUNGAGUNG - Diesty Hayuhantika; Dwi Shinta Rahayu (Universitas Insan Budi Utomo, 2019)
Mathematical learning is abstract. A learning innovation is needed by considering aspects of daily life so abstract mathematical concepts can be understood by students. Mathematics and culture are two interrelated things, the bridge between the two is called ethnomatematics. The focus of the research is on the 6 main elements of Reyog Tulungagung. This research is a qualitative research with ethnographic approach. The results of research in the form of mathematical ideas which are found based on the physical form of Reyog Tulungagung art elements, including: (1) mathematical ideas in gong, namely circles, arcing curved spaces, volumes of rotating objects, and symmetry; (2) mathematical ideas on the selompret, namely construct curved side spaces, rotating objects volume, and symmetry; (3) mathematical ideas on kenong namely circles, build curved side spaces, and rotary object volumes; (4) mathematical ideas on iker namely lines, circumference of circles, and symmetry; (5) mathematical ideas on dhodhog, that are circles, arcing curves, volume of rotating objects, triangles, and one-to-one correspondence; (6) mathematical ideas on goseng namely counting and arithmetic (addition and multiplication). In addition there is also a mathematical idea of how to play musical instruments, namely repetitive patterns.